Active‐Phase Formation and Stability of Gd/Pt(111) Electrocatalysts for Oxygen Reduction: An In Situ Grazing Incidence X‐Ray Diffraction Study. Issue 47 (6th July 2018) - Escudero‐Escribano, María; Pedersen, Anders F.; Ulrikkeholm, Elisabeth T.; Jensen, Kim D.; Hansen, Martin H.; Rossmeisl, Jan; Stephens, Ifan E. L.; Chorkendorff, Ib
Abstract: Alloys of platinum and gadolinium present significant activity enhancement over pure Pt for the oxygen reduction reaction (ORR), both in the form of extended electrode surfaces and nanoparticulate catalysts. The active phase consists of a compressed Pt overlayer formed on Pt5 Gd electrodes upon exposure to the electrolyte by acid leaching. Here, we investigate the formation, strain and correlation lengths of the active Pt overlayer by using in situ synchrotron grazing incidence X‐ray diffraction on Gd/Pt(111) single‐crystalline electrodes. The overlayer forms upon exposure to electrolyte under open circuit conditions; the compressive strain relaxes slightly upon repeated electrochemical cycling in the potential range 0.6 to 1.0 V versus the reversible hydrogen electrode (RHE). In addition, the strain relaxes strongly when exposing the electrode to 1.2 V versus RHE, and the thickness of the crystalline portion of the overlayer increases with potential above 1.3 V versus RHE. Abstract : Watching it evolve : The graphic shows a schematic view of the in situ surface‐sensitive X‐ray diffraction setup used to characterise the Pt overlayer formed on Gd/Pt(111) alloys. This method allows one to monitor the formation and evolution of the structure of the active phase under electrochemical conditions.